PROPOSAL OF A HYBRID RECTIFIER STRUCTURE WITH HPF AND LOW THD SUITABLE FOR FRONT-END TROLLEYBUSES SYSTEMS SUPPLIED BY AC DISTRIBUTION NETWORKS - Freitas, Luiz C. G.; Lima, Gustavo B.; Goncalves, Flavio A. S. [UNESP]; Melo, Guilherme A. [UNESP]; Canesin, Carlos A. [UNESP]; Freitas, Luiz C. de; IEEE (Ieee, 2009)
This paper presents the development and the experimental analysis of a new single-phase hybrid rectifier structure with high power factor (PF) and low harmonic distortion of current (THDI), suitable for application in traction systems of electrical vehicles pulled by electrical motors (trolleybus), which are powered by urban distribution network. This front-end rectifier structure is capable of providing significant improvements in trolleybuses systems and in the urban distribution network costs, and efficiency. The proposed structure is composed by an ordinary single-phase diode rectifier with parallel connection of a switched converter. It is outlined that the switched converter is capable of composing the input line current waveform assuring high power factor (HPF) and low THDI, as well as ordinary front-end converter. However, the power rating of the switched converter is about 34% of the total output power, assuring robustness and reliability. Therefore, the proposed structure was named single-phase HPF hybrid rectifier. A prototype rated at 15kW was developed and analyzed in laboratory. It was found that the input line current harmonic spectrum is in accordance with the harmonic limits imposed by IEC61000-3-4. The principle of operation, the mathematical analysis, the PWM control strategy, and experimental results are also presented in this paper.
Keywords: Power Factor Correction; Hybrid Rectifiers; Urban Electrical Transportation Systems; Electrical Vehicles; Trolleybus